Investigation of the prevalence of Fowl adenovirus diseases in Iranian broiler chicken farms: a systematic review - Hamideh Najafi; Iman Pouladi; Maryam Hataminejad; Amin Jaydari (Journal of Applied Poultry Research)
SUMMARY: Fowl adenoviruses (FAdVs) cause a range of clinical symptoms, and viruses are becoming of great economic significance for the poultry industry. Hepatitis hydropericardium syndrome (HHS), inclusion body hepatitis (IBH), adenoviral gizzard erosion (AGE), lung disorders, and bleeding in the muscles and organs are among the diseases that are typically brought on by FAdVs. This study aims to investigate the spread of FAdV infections on broiler farms in Iran. The results of this research indicate that most of the diseases related to avian adenovirus (FAdV) in Iran include inclusion body hepatitis, adenoviral gizzard erosion, and Hepatitis-Hydropericardium Syndrome. According to the findings of this study, the most common disease related to FAdV in Iran is more than 70% inclusion body hepatitis, and after inclusion body hepatitis, adenoviral gizzard erosion is the most common in Iran. Additionally, it was found that serotypes 11 and 8b, as well as genotypes d and e, are the most common genotypes and serotypes linked to inclusion body hepatitis in Iran. Additionally, serotype 1 (FAdV-1) was shown to be the most often isolated serotype related to AGE disease in Iran throughout this study. Serotype 4 (FAdV-4) has been identified as the primary serotype linked to HHS isolates in Iran based on the findings of the previously described investigation. There is an urgent need to effectively monitor the FAV in slaughter-aged chickens across this country. Field isolates can also be recognized and classified using molecular techniques and virus isolation methods. Vaccinating broiler flocks in advance is the only effective strategy to control this disease. Regularly following vaccination schedules and the use of potent vaccinations are also recommended.